Utility and effectiveness of auditory measures for detecting 'Hidden hearing loss' and/or Cochlear Synaptopathy - Biagio de Jager, Leigh (University of Pretoria, 2020)
Dissertation (MA (Audiology))--University of Pretoria, 2019.